«The restoring democracy» History and politics in Uruguay’s democratic transition (1980-1989) - Garategaray, Martina (Universidad Pedagógica y Tecnológica de Colombia, 2021)
This article focuses, firstly, on the revision of the readings made by politicians, intellectuals and academics of the transition to democracy in Uruguay, commonly understood as the period between 1980 and 1989. An analysis is madeof the type of frameworks of meanings and imaginaries on which re-democratization was structured, and what recurrent and hegemonic readings –from history and political science–were installed in those years. It is possible to conclude that in Uruguay an interpretation of transitional democracy as normative or institutional democracy prevailed and that because it took pride in its institutionalist tradition and the «uniqueness of the country», it found its legitimating roots in the past. In the interpretations of the time, betting on a continuist outlook, the post-dictatorial future retreated in a naturalized manner to a known, predictable and, fundamentally, exceptional past. For this reason, in a second part, the article discusses these canonic points of view. From a perspective focused on political language, it is proposedto problematize the modeling of the transition towards democracy to reinstate the complex and central position of the political change in the democratic conceptualization. Thus, it is sought to review the years of the return to democracy in Uruguay with new questions which can shed light on little explored elements of the process, as well as to start a dialog about the Uruguayan experience with the transitions of the region as a kind of circulation and exchange of ideas among the intellectuals of the time.